Rethinking the Relationships Between Time Perspectives and Well-Being: Four Hypothetical Models Conceptualizing the Dynamic Interplay Between Temporal Framing and Mechanisms Boosting Mental Well-Being - Burzynska, Bozena; Stolarski, Maciej (Frontiers in Psychology, 2020)
Time perspective (TP) is a central aspect of human daily psychological functioning, with a pronounced impact on human thoughts, feelings, and behaviors. The particular TP dimensions are strongly associated with a range of various mental well-being indicators and were shown to predict as much as 40% of their variance. However, the relationship between TPs and specific mechanisms that enhance mental well-being still requires further exploration. In the present article, we conceptually analyze a potential interplay of TPs and three well-confirmed well-being “boosters” (WBBs)—gratitude, savoring the moment, and prioritizing positivity—which may prove responsible for the vital effects of TP on mental well-being. Each of the “boosters” has a clear temporal anchoring: gratitude stems from the appreciation of the past, savoring the moment refers mainly to the experience of the present, and prioritizing positivity engages planning behaviors that require future focus. We propose four theoretical models to be verified in further experimental research. The first model, the trait-behavior model, proposes that trait TPs increase the tendency to use particular WBBs in order to increase mental well-being. The second model, referred to as the accumulation model, offers that TPs mediate between WBBs and mental well-being; and finally, a regular practice of a specific WBB develops a specific TP (e.g., exercising a gratitude intervention enhances past-positive TP). The third model, the feedback loop, suggests that WBBs and TPs strengthen one another and contribute to higher mental well-being. The last model, which can be called the match–mismatch model, presents the influence of WBBs on mental well-being, where a particular TP plays a role of a moderator (e.g., present-hedonistic TP moderates the relationship between savoring and well-being). Implications of potential confirmation of each of the models for theory and practice are also discussed.